Nearly Ring Homomorphisms and Nearly Ring Derivations on Non-Archimedean Banach Algebras - Madjid Eshaghi Gordji (Abstract and Applied Analysis)
We prove the generalized Hyers-Ulam stability of homomorphisms and derivations on non-Archimedean Banach algebras. Moreover, we prove the superstability of homomorphisms on unital non-Archimedean Banach algebras and we investigate the superstability of derivations in non-Archimedean Banach algebras with bounded approximate identity.